A review of the genus Speocarcinus Stimpson, 1859 (Crustacea: Brachyura: Xanthidae), with a key to its species and the description of one new species - Brandão, Marianna; Coelho-Filho, Petronio Alves; Tavares, Marcos (Zootaxa, 2012)
Speocarcinus dentatus n. sp. is described from the southwestern Atlantic. The new species can be easily separated fromits congeners by a suite of carapace and appendage characters. Speocarcinus Stimpson, 1859, now includes eight extantspecies, all from the Atlantic or Pacific coasts of the Americas. Additional characters to further differentiate between S.carolinensis Stimpson, 1859, and S. lobatus Guinot, 1969, and between S. granulimanus Rathbun, 1894, and S. spinicar-pus Guinot, 1969 are documented. The lectotype of S. granulimanus is first described and a key to the species of Speocarcinus is provided.